Institutional Usage of Ferric Pyrophosphate Citrate (FPC) Delivered Via Dialysate in Reducing Erythropoiesis Stimulating Agents (ESAs) and IV Iron Cost. (June 2022) - Wang, Shan; DellaFera, Louis; Dhanani, Lameesa; Malone, Brian; Dutka, Paula; Akerman, Meredith; Masani, Naveed
Dialysis patients are often iron deficient due to a multiple factors. Ferric pyrophosphate citrate is a complex iron salt that can be given via dialysate allowing maintenance of hemoglobin (Hgb) concentration and iron balance while reducing the need for IV iron. The purpose of this study is to perform a cost evaluation of FPC and the effect it has on lowering the dose/use of ESAs and IV iron therapy. This study reviewed the same 100 hemodialysis patient's charts before and after the use of FPC. The data points that were collected and analyzed are as follows: hemoglobin, ferritin levels, average weekly ESA dosing, and IV iron replacement therapy dose. Out of 100 patients, there was no statistical difference in the average hemoglobin, ferritin, and iron saturation levels observed in the patients before and after FPC use. The average weekly dose of darbepoetin alfa per patient was 52.74 μg before the FPC group compared to 39.27 μg in the post FPC group ( P  < .0001). The total dose of ferric gluconate per patient was 3290.01 mg in the before FPC group and 585.60 mg in the post FPC group ( P  < .0001). The average total iron sucrose dose per patient in the before FPC group was 3097.92 mg versus 1216.67 mg in the post FPC group ( P  < .1563). When comparing FPC's cost and implementation into both of our outpatient dialysis centers, this yielded a net savings of $296 751.49.